Rationally tuning the atomic ratio of electrodeposited NiP for greatly enhanced hydrogen evolution in alkaline media. Issue 87 (17th October 2018) - Liu, Qian; Tang, Chun; Lu, Shiyu; Zou, Zhuo; Gu, Shuang; Zhang, Yuhuan; Li, Chang Ming
Abstract : Tuning the atomic ratio of an electrodeposited Ni x P y alloy toward a greatly enhanced hydrogen evolution reaction. Abstract : Rationally tuning the atomic ratio of electrodeposited Ni x P y for an optimal composition (Ni90 P10 ) greatly enhances hydrogen evolution. Density functional theory calculations shed light on the enhancement mechanism, that in comparison to other examined atomic ratios Ni90 P10 has a more moderate free energy of H adsorption and easier adsorption of water molecules toward greatly improved hydrogen production.